Herbal Remedies for Covid- 19: Perception and Self-Use - Shilpa bharti (International Journal of Pharma and Bio Sciences, 2021)
COVID-19 is an infectious disease caused by the newly discovered coronavirus strain. Herbal remedies have long been used to treat viral infections such as the common cold, flu, fever and even infections caused by herpes. Considering the importance and severity of the outbreak, Government of India has already issued directions to promote the use of herbal remedies as a supportive measure in self-care and treatment of the masses. The purpose of this study was to assess the knowledge, perception and self-use among educated adults towards the use of herbal remedies in the prevention or treatment of COVID-19 infection. Data regarding the perception and self-use of herbal remedies was collected from the general public using a 20-item online questionnaire. Totally 377 individuals responded to the survey. Descriptive and spearman’s correlation statistics was used for data analysis. Most of the respondents were in the age group of 18-30 years, with majority being females (60.5%). Around 59.7 % of the participants were using herbal remedies and 50.4% respondents were graduates. A total of 25 types of herbal remedies were used and the main source of information was elders at home or the mass media. 59.2% of the participants stated that herbal remedies are effective in the prevention or management of COVID-19 while 34.2% were not sure about it. 58% of the respondents felt that herbal remedies are safe and have no side effects, while 55.4% were not sure and only 32.7% people believed that herbal remedies can be used for COVID-19 supportive treatment. 68.3% of the participants did not consult their physician for the use of these remedies. Even though, a high level of herbal remedies usage was found among the respondents, they were not sure about its effectiveness in the prevention or treatment.